2006
DOI: 10.1128/aem.72.1.96-101.2006
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Conversion of Glycerol to 1,3-Propanediol: Physiological Comparison of a Natural Producer, Clostridium butyricum VPI 3266, and an Engineered Strain, Clostridium acetobutylicum DG1(pSPD5)

Abstract: Clostridium acetobutylicum is not able to grow on glycerol as the sole carbon source since it cannot reoxidize the excess of NADH generated by glycerol catabolism. Nevertheless, when the pSPD5 plasmid, carrying the NADH-consuming 1,3-propanediol pathway from C. butyricum VPI 3266, was introduced into C. acetobutylicum DG1, growth on glycerol was achieved, and 1,3-propanediol was produced. In order to compare the physiological behavior of the recombinant C. acetobutylicum DG1(pSPD5) strain with that of the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 37 publications
2
63
2
5
Order By: Relevance
“…with glycerol as the sole carbon source has resulted in 1,3-PDO titers greater than 60 g/l from both isolated and engineered strains of K. pneumoniae [31][32][33], C. butyricum [31,[34][35][36][37], and recombinant Clostridium acetobutylicum [34,38]. Due in part to the large number of studies and interest in the conversion of glycerol into 1,3-PDO, this topic has also been extensively reviewed [20,39].…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…with glycerol as the sole carbon source has resulted in 1,3-PDO titers greater than 60 g/l from both isolated and engineered strains of K. pneumoniae [31][32][33], C. butyricum [31,[34][35][36][37], and recombinant Clostridium acetobutylicum [34,38]. Due in part to the large number of studies and interest in the conversion of glycerol into 1,3-PDO, this topic has also been extensively reviewed [20,39].…”
Section: Trends In Biotechnologymentioning
confidence: 99%
“…Recent studies also have shown that glycerol dehydratases undergo irreversible suicide inactivation by glycerol (9,17,31), despite glycerol being the substrate and the dehydratase being essential for glycerol breakdown. Finally, one of the key limitations of the application of this biological process to industry is that it requires the coenzyme B 12 -dependent glycerol dehydratase, necessitating the addition of large amounts of a high-cost molecule, vitamin B 12 , to the culture medium. Hence, to establish an ideal bioprocess for 1,3-PD production, at least three challenges need to addressed: (i) the effect of accumulated 3-HPA on glycerol dehydratase activity; (ii) the inactivation of glycerol dehydratase by glycerol (8); (iii) the expense of coenzyme vitamin B 12 in fermentation.…”
mentioning
confidence: 99%
“…Thus, we sought to engineer a novel bacterial strain with an improved 1,3-PD yield. Toward this end, we cloned the following three genes: (i) dhaB1, which encodes the vitamin B 12 -independent glycerol dehydratase, from C. butyricum; (ii) dhaB2, which encodes an activating factor for vitamin B 12 -independent glycerol dehydratase, from C. butyricum; (iii) yqhD, which encodes the 1,3-propanediol oxidoreductase isoenzyme, an NADP-dependent dehydrogenase, from wildtype E. coli. The product of yahD is also called 1,3-propanediol NADP-dependent dehydrogenase and is sufficient to catalyze the interconversion of 3-HPA (25).…”
mentioning
confidence: 99%
“…However, new applications are being studied for large volumes of biodiesel glycerol, since it can't be used in food and cosmetics industries without a cleaning and refining process [7]. Glycerol may be used as carbon source in bioprocesses, and several species among the genera Clostridium, Citrobacter, Klebsiella and Pseudomonas [5,[7][8][9][10][11][12][13] are being studied for the biotransformation of glycerol from biodiesel to specialty chemicals. One promising solution is the use of biodiesel glycerol to produce 1,3-propanediol (1, by Klebsiella pneumoniae and Clostridium butyricum [14,15].…”
Section: Introductionmentioning
confidence: 99%